Immune-mediated retinopathy in a patient with stiff-man syndrome - Steffen, Heimo; Menger, N.; Richter, W.; Nölle, B.; Krastel, Hermann; Stayer, Catherine; Kolling, Gerold; Wässle, H.; Meinck, Hans-Michael (Graefe's archive for clinical and experimental ophthalmology, 1999)
Background: Stiff-man syndrome is a rare neurological disorder characterised by rigidity and violent spasms of the body musculature. In the majority of patients, presence of antibodies against glutamic acid decarboxylase (GAD), the enzyme synthesizing γ-aminobutyric acid (GABA), suggests an autoimmune attack against GABA-ergic inhibitory neurons. We report a 32-year-old patient with stiff-man syndrome and anti-GAD antibodies who developed subacute progressive loss of vision in the right eye, and in the left eye 18 months thereafter. · Methods: Ophthalmological work-up included electro-retinogram (ERG), visual evoked potentials (VEP) and fluorescein angiography. Antiretinal antibodies were investigated using an indirect immunofluorescence technique on frozen sections of macaque retina with patient´s serum and FITC-conjugated goat antihuman immunoglobulin. Staining with monoclonal anti-GAD65 antibodies and with serum from three healthy normals served as controls. · Results: Visual acuity of both eyes decreased to 0.16 within a span of 6 weeks. Perimetry revealed a central scotoma in the visual field of both eyes. VEP and flash ERG were progressively disturbed on the right eye. On the left eye, initially only pattern ERG and photopic responses were abnormal. Follow-up recordings revealed widespread pathology of photopic single and flicker responses. Immunofluorescence revealed strong reactivity of the inner plexiform layer and to a lesser extent staining of the outer plexiform layer at dilutions of 1:1000 with patients serum. The same retinal staining pattern was obtained with monoclonal anti-GAD65 antibodies. · Conclusions: These findings suggest autoimmune retinopathy, mediated by anti-GAD65 autoantibodies as the underlying cause of visual loss.
Gesehen am 09.03.2021